2022
DOI: 10.1088/1361-6528/ac83c8
|View full text |Cite
|
Sign up to set email alerts
|

A facile fabrication of ratiometric electrochemical sensor for sensitive detection of riboflavin based on hierarchical porous biochar derived from KOH-activated Soulangeana sepals

Abstract: Herein, a facile ratiometric electrochemical method was developed for sensitive sensing of riboflavin (RF) based on hierarchical porous biochar (HPB) modified electrode. In this sensing system, the reference paracetamol (PA) was directly added into electrolyte solution without the requirement of complex immobilization process. HPB derived from KOH-activated Soulangeana sepals displays hierarchical porous structure, high specific surface area and rich oxygen-containing functional groups, which is favorable for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Although the biomass will be self-activated when carbonized at high temperatures, the pore structure obtained by such self-activation is uncontrollable. In contrast, the use of various activators, such as KOH [ 20 ], KCl [ 21 ], ZnCl 2 [ 22 ], and K 2 CO 3 [ 23 ], could realize the orderly adjustment of porous structure in the preparation of biochar.…”
Section: Introductionmentioning
confidence: 99%
“…Although the biomass will be self-activated when carbonized at high temperatures, the pore structure obtained by such self-activation is uncontrollable. In contrast, the use of various activators, such as KOH [ 20 ], KCl [ 21 ], ZnCl 2 [ 22 ], and K 2 CO 3 [ 23 ], could realize the orderly adjustment of porous structure in the preparation of biochar.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the new biochar had a higher specific surface area and micropore structure, which were 689.9 m 2 /g and 6.0 Å, respectively. He and his coworkers [ 7 ] studied KOH activated porous carbon and found that the hierarchical porous biochar extracted from the KOH activated Soulangeana sepals had a hierarchical porous structure, high specific surface area, and abundant oxygen-containing functional groups. Jie et al [ 8 ] showed that the thermal decomposition of plastic, as a common waste, and a representive hydrogen-rich energy raw material with high hydrogen content (8%~14%) could produce hydrogen-rich gas.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic and organic pollution factors, such as heavy metals, toxic dyes, pesticides, etc., are harmful to the human health as well as ecological systems. , Therefore, many technologies and materials have been developed to solve water pollution issues. Biochar is a traditional adsorbent for treatment of many pollutants due to its high carbon content, nontoxicity, low cost, and environment friendliness and thus has a high wastewater treatment potential. For instance, cattle manure-derived biochar was employed as an adsorbent for the removal of methylene blue (MB) from aqueous solutions . Coconut husk-derived biochar was also applied for the remediation of ciprofloxacin and tetracycline in wastewater …”
Section: Introductionmentioning
confidence: 99%
“…Biochar is a traditional adsorbent for treatment of many pollutants due to its high carbon content, nontoxicity, low cost, 3 and environment friendliness and thus has a high wastewater treatment potential. 4 6 For instance, cattle manure-derived biochar was employed as an adsorbent for the removal of methylene blue (MB) from aqueous solutions. 7 Coconut husk-derived biochar was also applied for the remediation of ciprofloxacin and tetracycline in wastewater.…”
Section: Introductionmentioning
confidence: 99%